(untitled) (UNED Research Journal, 2016)
The occurrence of Lagocephalus inermis (Temminck & Schlegel, 1850) is reported for the first time from Digha extending the range of the species to the east coast of India based on one specimen. This species was already reported from south-eastern coast of India and western coast of India. The 196 mm standard length specimen from Digha Mohana is described in detail.